Associations Between Sleep Duration and Cardiometabolic Diseases Among Residents in Southwest China - Li J; Lu Y; Zhang X; Liu G (Nature and Science of Sleep, 2024)
Jinxi Li,1,* Yiduo Lu,2,* Xuyun Zhang,1 Gang Liu3 1International Medical College, Chongqing Medical University, Chongqing, People’s Republic of China; 2College of Basic Medical Sciences, Naval Medical University, Shanghai, People’s Republic of China; 3Department of Cardiology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Gang Liu, Email 203745@hospital.cqmu.edu.cnIntroduction: The burden of cardiometabolic diseases (CMDs), defined as stroke, coronary artery disease, and diabetes mellitus, continues to pose a global challenge. Sleep duration has been linked to cardiovascular health. However, there is a lack of focused investigations on CMDs in underdeveloped areas of China.Purpose: This study aimed to examine the relationship between sleep duration and CMDs among residents from southwest China.Patients and Methods: This large cross-sectional study screened data from the National Key Research and Development Program (2018YFC1311400). Based on sleep duration reported through a standardized questionnaire, encompassing the sleep patterns of the past five years, participants were classified into three groups: < 6, 6– 8, > 8 hours. Baseline characteristics were compared, and Poisson regression models were used to assess the relationship between sleep duration and CMDs. Subgroup analysis was conducted based on age and gender.Results: This study included 28,908 participants with an average age of 65.6 ± 10.0 years, of whom 57.6% were female. The overall prevalence of CMDs was 22.6%. After multivariate adjustments, the prevalence ratios (PR) (95% CI) for CMDs across the three groups (6– 8h, < 6h and > 8h) were: reference, 1.140 (1.068– 1.218), 1.060 (0.961– 1.169) (P for trend =0.003), respectively. The subgroup analysis revealed that among older females, a longer sleep duration (> 8h) was also associated with an increased prevalence risk of CMDs, with PR 1.169 (1.001– 1.365) (p=0.049).Conclusion: A shorter sleep duration (< 6 hours) was associated with an increased risk of CMDs in the general population, while a longer sleep duration (> 8 hours) also raised the prevalence risk among older females.Keywords: cardiometabolic disease, sleep duration, Southwest China